Penguatan Pendidikan Gender di MI NU An Nur Purworejo - Muhammad Zaironi; Adib Qosim M; Muhammad Febri Irawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the strengthening of gender education at MI NU An Nur Purworejo, focusing on students’ and teachers’ understanding, teaching practices, and the madrasa culture that supports gender equality. The research background indicates that although gender education regulations exist, gender stereotypes still appear, such as leadership roles being more frequently assigned to male students. The study employs a descriptive qualitative approach with 32 fourth- and fifth-grade students and four teachers as subjects, using data collection techniques including questionnaires, semi-structured interviews, and classroom observations. Data analysis was conducted thematically and through triangulation. The results show that most students understand the principles of gender equality, yet some still hold traditional stereotypes. Simple interventions, such as leadership rotation and inclusive routines, were proven effective in increasing gender awareness. These findings provide a new perspective on contextual strategies for strengthening gender education in NU-based madrasas and emphasize the importance of integrating gender education from the early grades to achieve sustainable inclusive practices.